Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Tabungan Unit Usaha Syariah Bank Jambi - Susilawati Susilawati; Pupu Sopini (J-MAS (Jurnal Manajemen dan Sains), 2021)
The purpose of this study is to analyze the quality of service and satisfaction levels of savings customers of Bank Jambi's Sharia Business Unit and analyze the effect of service quality on the satisfaction of savings customers of Bank Jambi's Sharia Business Unit both simultaneously and partially. The selection of Bank Jambi Sharia Business Unit as an object of research because Bank Jambi is a regional bank that should host in its own area, but in its business operations must still prioritize service to customers in the face of many competitors in Jambi City, including Islamic banking. The research method used is a quantitative descriptive anaisis with a population of all savings customers of Bank Jambi's Sharia Business Unit in 2020 which amounted to 23,220 accounts (people). The sample withdrawal method uses the Slovin Formula with the results of calculations as many as 100 respondents. Based on the results of primary data research for service quality free variables, service quality variables produced the highest score on compliance variables of 449.5. This shows that the management of Bank Jambi's Sharia Business Unit is able to meet Islamic law and operate under the principles of Islamic economics and banking in serving its customers. While the lowest score of 419.25 is in the Reliability variable, but this score is still in the scale range with a very good category. As for the customer satisfaction variable, the average score of 442.75 from the respondents' responses with categories was very satisfied. Based on the results of the hypothesis test, from the results of data processing it is known that sig value. 0.000 < 0.05 (significance level) which means that simultaneously the free variable has a significant effect on customer satisfaction of Bank Jambi's Sharia Business Unit. The regression coefficient value of the six free variables used is known that the empathy variable has the largest regression coefficient which is 0.335. This shows that the empathy variable has the most influence on customer satisfaction savings of Bank Jambi's Sharia Business Unit. While the physical proof variable has the smallest regression coefficient of - 0.128. This means that physical facilities are not the dominant factor in determining the level of customer satisfaction in using banking services at Bank Jambi's Sharia Business Unit.